2018
DOI: 10.1029/2018jd028388
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Global Tropospheric OH Expected as a Result of Climate Change Over the Last Several Decades

Abstract: The oxidizing capacity of the troposphere is controlled primarily by the abundance of hydroxyl radical (OH). The global mean concentration of tropospheric OH, [OH]TROP (the burden of OH in the global troposphere appropriate for calculating the lifetime of methane) inferred from measurements of methyl chloroform has remained relatively constant during the past several decades despite rising levels of methane that should have led to a decline. Here we examine other factors that may have affected [OH]TROP such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 130 publications
7
71
0
Order By: Relevance
“…As OH destruction is likely modulated by strong changes in meteorology (C. D. Holmes et al, 2013), such as may have taken place in the past decade in tropical midtropospheric moisture and cloud structure, it is possible that significant interannual variability in OH destruction may indeed occur, though detailed mechanisms capable of driving such large changes in the oxidative capacity of the atmosphere have not been proposed. However, in this context, Nicely et al (2018) and Lelieveld et al (2016) agreed with Montzka et al (2011) in finding that interannual variability of OH has probably been fairly small.…”
Section: Methane Sources and Sinks: The Insight From Carbon Isotopessupporting
confidence: 72%
See 1 more Smart Citation
“…As OH destruction is likely modulated by strong changes in meteorology (C. D. Holmes et al, 2013), such as may have taken place in the past decade in tropical midtropospheric moisture and cloud structure, it is possible that significant interannual variability in OH destruction may indeed occur, though detailed mechanisms capable of driving such large changes in the oxidative capacity of the atmosphere have not been proposed. However, in this context, Nicely et al (2018) and Lelieveld et al (2016) agreed with Montzka et al (2011) in finding that interannual variability of OH has probably been fairly small.…”
Section: Methane Sources and Sinks: The Insight From Carbon Isotopessupporting
confidence: 72%
“…In this context, Thompson et al () found that OH appears not to have contributed significantly to recent methane growth. Further insight into the OH problem came from Nicely et al () who showed that atmospheric OH is probably currently well buffered, with mean anomalies of 1.6%. Although OH would be expected to decrease as methane rises, this effect is countered by the tropical widening as the Hadley cells expand (R. J. Allen et al, ), combined with the influences of changing H 2 O, NO x , and overhead O 3.…”
Section: Testing the Hypotheses That May Explain The Recent Rise In Mmentioning
confidence: 99%
“…However, accounting for OH source variability results in methane emissions estimates with similar trend and variability to Rigby et al (2017) and Turner et al (2017), where OH concentrations are fitted directly without interactive chemistry. This is due to compensating OH production accounting for variabilities in (Holmes et al, 2013;Naik et al, 2013;Nicely et al, 2018) are not explicitly represented in our model, so the question "How does OH production and recycling vary over time?" remains and should be a priority research objective.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…In the coming years, estimation of [OH] using MCF will become more uncertain as its atmospheric mole fraction declines (Prinn et al, ). While some recent MCF, budget‐based studies have suggested that [OH] changes could be a major contributor to recent methane growth rate variability, albeit with very large uncertainty (Rigby et al, ; Turner et al, ), atmospheric photochemical models do not tend to find evidence for strong variability in global [OH] (e.g., Figure , Nicely et al, ). However, photochemical models disagree substantially in their predictions of the average global [OH] (Voulgarakis et al, ).…”
Section: Top‐down Source and Sink Estimation At Global And Regional Smentioning
confidence: 99%
“…Anomalies are presented to indicate the magnitude of interannual variability in [OH]. (Source: Julie Nicely, Nicely et al, ).…”
Section: Top‐down Source and Sink Estimation At Global And Regional Smentioning
confidence: 99%